Movement disorders in primary central nervous system lymphoma: two unreported cases and a review of literature - Grillo, Piergiorgio; DI Giuliano, Francesca; Massa, Roberto; Mercuri, Nicola Biagio; Schirinzi, Tommaso (Neurological sciences, 2021)
Background Recognition of secondary movement disorders (SMDs) is fundamental either to alleviate disabling disturbances or to treat potentially life-threatening conditions, such as brain tumors. Primary CNS lymphoma (PCNSL) is a rare form of CNS cancer that is often located in subcortical areas, accounting for both neuropsychiatric and motoric disorders. Nevertheless, an overview on PCNSL-related movement disorders (MDs) phenomenology has not been provided yet. Objective To outline the main features of PCNSL-related MDs. Methods A retrospective analysis was conducted on a cohort of patients with PCNSL presenting with MDs, including all existing cases identified by a systematic literature review (source: Medline; period: 1946–2020) and two unreported cases. Data on phenomenology, neuroimaging, histology, and clinical course were collected. Results A total cohort of fifteen subjects was defined, enrolling thirteen previously described patients extracted from eleven published studies, and our two unreported cases. A parkinsonian syndrome appearing at about 60 years of age, unresponsive to levodopa, associated to other neurological signs, resulted as the most common presentation of PCNSL-related MD. Chorea, dystonia, and dyskinesia occurred less frequently, with some degree of responsiveness to symptomatic treatments. Basal ganglia were involved in most cases and motoric disturbances often ameliorated after tumor mass reduction. Conclusions This study identified those features of PCNSL-related MDs that could support an appropriate approach to such a rare condition. In fact, while the outcome remains still poor, the therapeutic scenario of PCNSL is changing; an early diagnosis together with an adequate management will be thus crucial for timely and successful interventions.